PENERAPAN MODEL QUANTUM TEACHING DALAM PENINGKATAN PEMBELAJARAN IPA PADA SISWA KELAS IV SDN 3 KARANGSAMBUNG - Rofingah, Siti (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: Application of Quantum Teaching Models in Science Teaching Enhancement on Class IV students of SDN 3 Karangsambung. This study aims to: improve science learning in class IV using quantum model of teaching. This study was conducted in three cycles. The subjects were all fourth grade students at SDN 3 Karangsambung totaling 28 students. Source data came from students, peers, and researchers. Data collection techniques using observation, documentation, and testing. Analysis of the data used by qualitative and quantitative. Percentage of completeness students in the first cycle were 87.4%, 82.3% second cycle and third cycle was 83.9%. The result shows that the application of teaching model quantum, can improve student learning outcomes in science teaching in class IV. Keywords: Quantum Teaching, Learning Outcomes, IPA. Abstrak: Penerapan Model Quantum Teaching dalam Peningkatkan Pembelajaran IPA pada Siswa Kelas IV SDN 3 Karangsambung. Penelitian ini bertujuan: meningkatkan pembelajaran IPA dikelas IV dengan menggunakan model quantum teaching. Penelitian ini dilaksanakan dalam tiga siklus. Subjek penelitian ini adalah seluruh siswa kelas IV SDN 3 Karangsambung yang berjumlah 28 siswa. Sumber data berasal dari siswa, teman sejawat, dan peneliti. Teknik pengumpulan data menggunakan observasi, dokumentasi, dan tes. Analisis data yang digunakan dengan kualitatif dan kuantitatif. Persentase ketuntasan siswa pada siklus I adalah 87,4%, siklus II 82,3%, dan siklus III adalah 83,9%. Hasilnya menunjukan bahwa penerapan model quantum teaching, dapat meningkatkan hasil belajar siswa dalam pembelajaran IPA di kelas IV.   Kata Kunci: Quantum Teaching, Hasil Belajar, IPA.